Changing the Terms Translating in the Postcolonial Era - Simon, Sherry (Translating in the Postcolonial Era, 2001)
This volume explores the theoretical foundations of postcolonial translation in settings as diverse as Malaysia, Ireland, India and South America. Changing the Terms examines stimulating links that are currently being forged between linguistics, literature and cultural theory. In doing so, the authors probe complex sequences of intercultural contact, fusion and breach. The impact that history and politics have had on the role of translation in the evolution of literary and cultural relations is investigated in fascinating detail.